2003
DOI: 10.1542/peds.112.3.e192
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Socioeconomic Status on the Effectiveness of Bicycle Helmet Legislation for Children: A Prospective Observational Study

Abstract: ABSTRACT. Objective. To evaluate the influence of average family income in a geographic area on the effectiveness of helmet legislation on observed helmet use by children (5-14 years).Methods. The study was conducted in East York, a health district of Metropolitan Toronto, in collaboration with the East York Health Unit. In 1996, the total population was 107 822, 11 340 of which were children 5 to 14 years. Census data were used to group the 21 census tracts in East York into 7 geographically distinct areas. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 23 publications
2
38
2
Order By: Relevance
“…This is consistent with other literature demonstrating that only a small percentage of cyclists and motorcyclists use high visibility clothing (Mayr et al, 2003;McGuire and Smith, 2000;Reeder et al, 1996;Wells et al, 2004). We have also found that most observed cyclist and pedestrian characteristics have at least substantial inter-observer agreement, consistent with the findings of other investigators (Coté et al, 1992;Parkin et al, 2003;Puder et al, 1999). Finally, a major trunk color of orange, red, yellow or white appears to be a consistent predictor of observer assessed visibility in both cyclists and pedestrians.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with other literature demonstrating that only a small percentage of cyclists and motorcyclists use high visibility clothing (Mayr et al, 2003;McGuire and Smith, 2000;Reeder et al, 1996;Wells et al, 2004). We have also found that most observed cyclist and pedestrian characteristics have at least substantial inter-observer agreement, consistent with the findings of other investigators (Coté et al, 1992;Parkin et al, 2003;Puder et al, 1999). Finally, a major trunk color of orange, red, yellow or white appears to be a consistent predictor of observer assessed visibility in both cyclists and pedestrians.…”
Section: Discussionsupporting
confidence: 92%
“…There was also likely some non-differential misclassification of neighborhood average annual income as it did not modify the pre-to post-legislation helmet prevalence. These results differ from findings of Parkin et al (2003) who noted a greater increase in the prevalence of helmet use post-legislation among low and middle compared to high SES areas.…”
Section: Limitationscontrasting
confidence: 99%
“…Our data show that a reduction of educational inequalities in injuries resulting in hospital admission can be achieved if injury prevention programs are able to reach those in the lower educational groups. It has recently been shown that lower socio-economic groups could benefit more from specific injury prevention measures than higher socio-economic groups [49]. More knowledge is required about the explanation of these inequalities before implementing prevention programs.…”
Section: Discussionmentioning
confidence: 99%